Clinical manifestations of childhood asthma persisting until the age of seven - Rini Asterina; Sjawitri P Siregar; Bambang Madiyono; Bambang Supriyatno (Paediatrica Indonesiana, 2004)
Background Asthma is a chronic illness commonly found in chil-dren. We aimed to find out the clinical manifestations of childhoodasthma persisting until the age of seven and the influencing factors.Methods A review was performed at the outpatient clinic of theDepartment of Child Health Cipto Mangunkusumo Hospital Jakarta,from January 1992 to December 2001, on children with asthmawho still had symptoms until the age of seven.Results During the period of 10 years, there were 322 childrenwith clinical symptoms of asthma persisting until the age of 7. Onehundred and forty-six (45.3%) met the inclusion criteria, consistingof 75 (51.4%) boys and 71 (48.6%) girls. The average age was11.7 years. There were 101 (69.2%) patients with rare episodicasthma, 26.0% with frequent episodic asthma, and 4.8% with per-sistent asthma. Age of onset was mostly beyond 3 year-old (51%).Besides asthma, atopic diseases noted in these patients were al-lergic rhinitis in 85 (58.2%) and atopic dermatitis in 42 (28.8%).Logistic regression found that cigarette smoke exposure (adjustedOR 4.72, 95%CI 2.05;10.87, p=0.000), allergic rhinitis (adjustedOR 3.44, 95%CI 1.40;8.45, p=0.007), and atopic dermatitis (ad-justed OR 2.37, 95%CI 1.01;5.72, p=0.048) had significant asso-ciation with the degree of asthma.Conclusion Of 146 children who still had asthma until the age ofseven, there were 69% with rare episodic asthma, 26% with fre-quent episodic asthma, and 4.8% with persistent asthma. Factorspresumably influencing this manifestations were cigarette smokeexposure, allergic rhinitis, and atopic dermatitis